Pengaruh Media Sosial dan Efikasi Diri terhadap Perilaku Konsumsi Siswa SMAN 3 Palangka Raya - Rozikin, Achmad Zainul; Suyati, Endang Sri (Universitas Pendidikan Ganesha, 2023)
Consumption behavior of students can be influenced by internal factors and external factors. There are several internal factors, one of which is self-efficacy, while external factors include the intensity of social media use. The purpose of this study was to determine how much influence self-efficacy and intensity of social media use on the consumption behavior of SMAN 3 Palangka Raya students. Data for the three variables (self-efficacy, intensity of use of social media, and consumption behavior) were obtained by distributing questionnaires to students of SMAN 3 Palangka Raya. The population of this study was 1635 students, while the sample was 509 students. Sampling technique using random sampling technique method. The results of this study indicate that consumption behavior can be influenced by self-efficacy and the intensity of using social media partially or simultaneously. The results also show that the contribution of the intensity of social media use is greater than self-efficacy